ZPC automated network logs and ICT support ticket tracking system - Mahlabvani, Tinashe (Midlands State University, 2018)
This project concentrates on developing the ZPC Automated Network Logs and ICT Support Ticket Tracking System which was seen necessary after it was discovered that the manual system that was being used for ticket tracking and network logging had weaknesses. Poor communication through the use of multiple communication mediums led to difficulties in tracking the support tickets raised by users at Zimbabwe Power Company. Also the manual system was also not effective in checking the status of servers since the ICT personnel would sometimes forget to manually ping the servers to check the availability. A feasibility study was carried out to assess if the project was technically, economically and operationally feasible. It was then seen favorable to continue with the project since to be feasible. Information was gathered using interviews, questionnaires and background reading to gather functional requirements of the system and problems faced by users with the old system. The design phase was conducted which included the system dataflow design, interface as well as database tables design. The Automated Network Logs and ICT Support Ticket Tracking System was developed using ASP.Net and C# with SQL Server Database. The system developed was tested thoroughly using unit testing, sub system testing, acceptance testing, validation and verification. This was carried out to see that system was working without errors whilst the specifications and objectives of the system were met. The system conversion methodologies were evaluated and a parallel changeover was recommended to install the system as it gives users time to familiarize with the system. Also this means that anomalies can be rectified during this period. The organization will have backup from the old system so it can revert to the old system if the new system fails. Maintenance strategies were discussed and it was seen necessary to use them to ensure the continuity of the system, efficiency and effectiveness. Recommendations were made so that the system will make ZPC a good environment for work through introducing a chat facility.